1994
DOI: 10.1159/000139213
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High-Dose Verapamil Administration on the Ca<sup>2+</sup> Channel Density in Rat Cardiac Tissue

Abstract: It is well known that β-adrenergic receptors will down-regulate in the presence of high circulating levels of β-adrenergic agonists over extended periods of time. However, less is known with respect to the effect of Ca2+ channel antagonists on their receptors. The purpose of this study was to determine if chronic administration of high dosages of verapamil (in the toxic range) could alter the density of Ca2+ channels in the heart as determined by [3H]PN 200-110 binding. A range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
2
6
0
Order By: Relevance
“…We did not observe any effect of verapamil on Cav1.2 mRNA or protein expression in vivo . Our results are in agreement with multiple prior studies showing that there is no change in calcium channel protein expression following in vivo verapamil treatment, as assessed by dihydropyridine binding analysis (McCaughran & Juno, 1988; Lonsberry et al 1992, 1994; Chapados et al 1992).…”
Section: Discussionsupporting
confidence: 93%
“…We did not observe any effect of verapamil on Cav1.2 mRNA or protein expression in vivo . Our results are in agreement with multiple prior studies showing that there is no change in calcium channel protein expression following in vivo verapamil treatment, as assessed by dihydropyridine binding analysis (McCaughran & Juno, 1988; Lonsberry et al 1992, 1994; Chapados et al 1992).…”
Section: Discussionsupporting
confidence: 93%
“…There are only few and controversial data from animal experiments about what effect long-term treatment with calcium channel blockers has on the biochemical characteristics and density of the myocardial calcium channels. [29][30][31][32][33] Our results would be best explained by an upregulation of calcium channels, as reported for long-term (ie, 25 days) nifedipine treatment in rabbits by Chiappe de Cingolani et al 33 As a clinical consequence of the decreased verapamil elimination during long-term oral treatment, a reduced or less frequent dosing has been suggested when steady-state conditions have been achieved in order to produce the desired serum concentrations and to minimize unwanted side effects. 15,17,18,21 Our combined kinetic and dynamic findings argue against a downward titration of the dose and provide the rationale that despite the accumulation of verapamil with multiple dosing maintenance of individual dosages from the beginning of the rate control therapy in patients with chronic atrial fibrillation may not only be clinically acceptable but even necessary.…”
Section: Discussionsupporting
confidence: 59%
“…Clinical trials using the drug combination strategy in humans (verapamil and adriamycin) and verapamil alone in mice (Lonsberry et al 1994) have demonstrated that the MDR modulators can exhibit toxic side effects. The combination of the anthelmintics and the MDR modulators has been studied in jirds and in sheep .…”
Section: Discus Discus Discus Discus Discussion Sion Sion Sion Sionmentioning
confidence: 99%